INDICADORES DE SUSTENTABILIDADE DE BACIA HIDROGRÁFICA E HIDROQUÍMICA DE POÇOS NO ESTADO DO MARANHÃO: Subsídios ao gerenciamento e conservação dos recursos hídricos - DIAS, Isabel Cristina Lopes (2018)
In view of the importance of water resources and their impacts both on the survival of Human beings as to the equilibrium of the environment as a whole, this research Evaluated water management in the state of Maranhão, through indicators of Hydric sustainability; and analyzed some physicochemical and microbiological parameters of Water wells of 3 areas of the state. Sustainability indicators focused on problems Socio-economic, hydrological and institutional studies were applied in six hydrographic basins of Maranhão: Parnaíba River basin, Itapecuru, Munim, Mearim, Tocantins and Gurupi, Obtaining intermediate general performance in the evaluated hydrographic basins. The water of Twenty-six wells, distributed in Zones 1, 2 and 3, was evaluated for the parameters Temperature, hydrogenionic potential, dissolved oxygen, electrical conductivity, solids Total dissolved, salinity, turbidity, chloride, nitrate and Escherichia coli concentration. The Results pointed out that the groundwater in the state of Maranhão has good Quality, despite changes in some parameters and low PH values observed Especially in Zone 3. It is concluded that it is necessary to adopt priority measures in the Hydrological dimension, especially in groundwater; Attention to sanitation including the public supply; Reducing the demands and waste of Water implementation of management tools; Consolidation and support to Basin Committees Watershed. This study has important implications for water management in the Maranhão, providing useful information on the sustainability of water, and with potential To support decision-making and water resource planning actions.